Cosmetic Talc-Related Pulmonary Granulomatosis - Sonia Jasuja MD; Brooks T. Kuhn MD; Michael Schivo MD, MAS; Jason Y. Adams MD, MS (SAGE Publishing, 2017)
Inhalation of cosmetic talc can lead to pulmonary foreign-body granulomatosis, though fewer than 10 cases of inhaled cosmetic talc-related pulmonary granulomatosis have been reported in adults. We report the case of a 64-year-old man with diffuse, bilateral pulmonary nodules and ground glass opacities associated with chronic inhalation of cosmetic talc. Transbronchial biopsy showed peribronchiolar foreign-body granulomas. After cessation of talc exposure, the patient demonstrated clinical and radiographic improvement without the use of corticosteroids. This case demonstrates that a conservative approach with cessation of exposure alone, without the use of corticosteroids, can be an effective therapy in cosmetic talc-related pulmonary granulomatosis.